Increased inventory turnover through a lean warehousing management model in SMES suppliers to the food industry - Vásquez Ortiz, Andrea Ximena (2023)
The present investigation is carried out in an importing and marketing company belonging to the food industry in Peru, which presented deficiencies in its warehouse management. These were reflected in the technical gap of its storage indicators compared to the average in the industry. For this reason, this study proposes a model based on the lean warehousing philosophy, supported by Kanban, 5S and supplier approval tools in order to achieve an improvement in warehouse management, which is reflected in the indicator of inventory turnover. It is important to highlight that the importance of this research lies not only in the approach of a management model for a sector that is rarely referred to in the literature, but also in the favorable applicability of this model based on a philosophy that allowed speeding up processes in warehouse, thus optimizing outbound logistics. In this way, it was possible to verify that the proposed model generates value for the company under study, so it will serve as a reference for the improvement of SMEs in the industry. The data analysis for the improvement was carried out using the Arena Simulation software, through which the favorable results were announced in each of the evaluator indicators: inventory turnover increased 8 times with respect to the initial level, equaling the turnover industry average of 12 times per year. On the other hand, the level of precision in the inventory count increased to 97.44%, which had a positive impact on the performance of the sales area due to the precision in the amount of inventory available. Finally, the choice of suppliers was improved, as evidenced by a 4.64% reduction in inventory loss.